Cryopreserved Ex Vivo-Expanded Allogeneic Myeloid Progenitor Cell Product Protects Neutropenic Mice from a Lethal Fungal Infection. Issue 1 (January 2016) - Domen, Jos; Christensen, Julie L.; Gille, Daphne; Smith-Berdan, Stephanie; Fong, Timothy; Brown, Janice M. Y.; Sedello, Anna K.
Severe neutropenia induced by chemotherapy or conditioning for hematopoietic cell transplantation often results in morbidity and mortality due to infection by opportunistic pathogens. A system has been developed to generate ex vivo-expanded mouse myeloid progenitor cells (mMPCs) that produce functional neutrophils in vivo upon transplantation in a pathogen challenge model. It has previously been demonstrated that transplantation of large numbers of freshly isolated myeloid progenitors from a single donor provides survival benefit in radiation-induced neutropenic mice. In the present work, an ex vivo-expanded and cryopreserved mMPC product generated from an allogeneic donor pool retains protective activity in vivo in a lethal fungal infection model. Infusion of the allogeneic pooled mMPC product is effective in preventing death from invasive Aspergillus fumigatus in neutropenic animals, and protection is dose dependent. Cell progeny from the mMPC product is detected in the bone marrow, spleen, blood, and liver by flow cytometry 1 week postinfusion but is no longer evident in most animals 4 weeks posttransplant. In this model, the ex vivo-generated pooled allogeneic mMPC product (i) expands and differentiates in vivo; (ii) is functional and prevents death from invasive fungal infection; and (iii) does not permanently engraft or cause allosensitization. These data suggest that an analogous ex vivo-expanded human myeloid progenitor cell product may be an effective off-the-shelf bridging therapy for the infectious complications that develop during hematopoietic recovery following hematopoietic cell transplantation or intensive chemotherapy.